Prevalence of root caries and associated factors among elderly population visiting a dental teaching hospital in Kathmandu, Nepal (Nepal Medical College Journal, 2023)
Among the oral ailments which are observed by dental practitioners in elderly, root caries is a significant one. It has been reported that about a third of older population bears most of the root caries burden. Root surface caries is one of the significant oral health problems in the elderly, and the incidence of root surface caries has been found to be one of the major risk factors for tooth loss. Limited studies have been carried out on root caries in elderly patients in context of Nepal. Hence, the objective of this study was to find the prevalence of root caries and its associated factors among the elderly population. This observational cross sectional study was done on 188 adult patients of 60 years and above. A specifically designed questionnaire was used to collect the following information: socio-demographic characteristics, use of medication, oral hygiene practices and oral health behaviour. Data were analyzed using Chi square test and descriptive statistics were calculated. It was found that the prevalence of root caries was 61.7% and it increased with age. There was an association between root caries and socioeconomic status which showed root caries was seen more in adults of upper middle class. More of root caries was seen in females, those who were unmarried, taking medications and non vegetarians. Oral hygiene habits and oral health behaviour had a positive impact on root caries. More of root caries was seen on buccal surface of molars.